Analisis Penerapan Perhitungan, Penyetoran, dan Pelaporan Pajak Pertambahan Nilai (PPN) pada PT. PMP Tahun 2023 - Deby Samarta; Uswatun Khasanah; Triana Yuniati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the implementation of Value Added Tax (VAT) calculation, payment, and reporting at PT. PMP during the 2023 tax year. This study uses a qualitative descriptive approach with data collection techniques through interviews, direct field observations, and documentation studies of the company's tax archives and financial reports. The main focus of the study is to determine the extent of the company's compliance with tax regulations issued by the Directorate General of Taxes. The results show that PT. PMP has carried out its tax obligations in accordance with applicable laws and regulations, including the use of the e-Faktur application for issuing electronic tax invoices and e-Filing for reporting VAT Periodic Tax Returns. In the VAT calculation process, the company systematically classifies output and input tax invoices. However, several conditions of overpayment and underpayment were found due to the dynamic variation between output and input VAT, especially in transactions involving discounts and sales returns. Tax payments were generally made on time through the online billing system, although there was a two-day delay in one tax period due to internal administrative constraints. While reporting is consistent each month, several input errors due to human error were still found, such as incorrectly entered Tax Invoice Serial Numbers (NSFP) or transaction values. These errors were then corrected through the Periodic Tax Return correction mechanism. Overall, the company has demonstrated a strong commitment to fulfilling its tax obligations, but improvements are still needed, particularly in coordination between tax divisions, data validation prior to reporting, and increasing human resource capacity in utilizing the tax information system.